Essence of Diplomacy - Jönsson, Christer. author. aut Link
IX, 207 p.
Keywords: Essence of Diplomacy explores the essential, timeless features of diplomacy, drawing on the historical record of over three millennia. In their effort at making international relations (IR) theory relevant to diplomacy, and diplomacy relevant to IR theory, the authors identify three essential dimensions of diplomacy: communication, representation and the reproduction of international society.